(3QSGdI aj GdCSWQdGHs - (3MjOQ Hf YHO GdQMef GdMSjfj GdLRQjs
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3deG cGf Yde GdGSWQdGH ai PGJg YdekG TQjakG s
(3BNQgG (B:s
(3hEf cGf Ydi hSW GdSeGA aGdbWH Ydi fUa GdfgGQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B67 - (3U(B72s
(3JQLeg ef GdaGQSjgs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B1020 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B39 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs